Retrograde replacement of the thoracic aorta. - Cooley, D A (1995)
A technique is described for replacement of the entire thoracic aorta. In this "pull-through" technique, which utilizes hypothermic circulatory arrest, the graft is implanted in a retrograde fashion, thus providing protection for the spinal cord and brain and avoiding injury to the vagus and phrenic nerves.